THE EFFECT OF INFLATION, EXCHANGE EXCHANGE, INTEREST RATE ON STOCK PRICE IN THE TRANSPORTATION SUB-SECTOR, 2018-2020 - Siska Tri Amanda; Chairil Akhyar; Rico Nur Ilham; Adnan (PT. Radja Intercontinental Publishing, 2023)
This study aims to examine the effect of inflation, exchange rates, interest rates on stock prices in the transportation sub-sector in 2018-2020. For the purposes of data analysis, quantitative methods were used. The data used is secondary data obtained from the website id.investing.com and data published by Bank Indonesia. The sample in this study were 11 transportation companies listed on the IDX for the 2018-2020 period. The sampling technique used purposive sampling. The data analysis method in this study is the panel data regression analysis method. The results of the study prove that partially, the inflation variable (X1) has a positive and significant effect on stock prices (Y), exchange rates (X2) has no significant negative effect on stock prices (Y), interest rates (X3), no significant positive effect on stock prices. Furthermore, the simultaneous test results prove that Ftable of 4.46 is much smaller than Fcount, namely 11.73007. So it can be concluded that simultaneously the independent variables namely Inflation, Exchange Rates, Interest rates have a positive and significant effect on the dependent variable, namely the stock price of registered transportation companies on the IDX in 2018-2020.